IMPROVING IRON AND MANGANESE QUALITY IN GROUNDWATER WITH NATURAL FILTERS METHOD - Femi Earnestly (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2021)
The resident in RT 001/ RW 013, Pasie Nan Tigo Subdistrict, Padang City generally has used the groundwater for daily need but that groundwater can not be used for the drinking, washing the clothes and for a bath because the water looked turbid, sandy and unpleasat odor. If the water condition like these conditions, it is usually caused by the overlimit of iron and manganese level in that water. Based of that problems we made natural water filter to treat that water by using sands, gravel, palm fiber, coconut shell charcoal in household scale. The purpose of this study is to know the effectiveness of natural water filters to remove the iron and manganese in the ground water. Natural filter material used in this study was arranged with varying thichnesses. As for determining the levels of iron and manganese in the sample carried out by the method of National Indonesian Standar 06-6989.4-2004 and 6989.5:2009. The results of three groundwater sample tests before and after filtering showed the reducing iron and manganese levels namely 58,21 % and 91,58 %. The value of iron and manganese in the sample after being tested is still below the quality standart for drinking water.